PERSEPSI SISWA SMP TERHADAP PROBLEM ENVIRONMENTAL INPUT PENDIDIKAN PADA PEMBELAJARAN IPA - Rimza Nuralifah Widyasari; Wahono Widodo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research aimed to determine the perception of Junior High School students on environmental problems of educational input in science learning. The type of this research was quantitative descriptive using survey methods. The number of samples used was 60 students in 8 grade with random sampling. This research used a distributing questionnaires as a data collection technique. The results of this research were the aspects of the state of the facilities and infrastructure in schools was classified as very high, in the aspect of learning facilities at home, the implementation of discipline in schools, student relationships with other school members was classified as high, while there were environmental problems of educational input that affect students in aspects parental education, relationships between family members, home atmosphere, and the learning process in schools was relatively low, resulting in learning difficulties and unsatisfactory results in science lessons.